Energy Resources of Iran and Their Environmental Impacts - V. P. Bubnov; M. A. Mehdizadeh (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents an analysis of main sources of energy resource production and their sale  in the domestic and export markets. The authors have analyzed type of domestic energy consumers and estimated their environmental impacts. The paper shows that the shift to alternative energy sources will reduce an ecological impact on the environment.